Determinasi Pengungkapan Pertanggungjawaban Sosial Perusahaan pada Sektor Kesehatan di Indonesia (Determinants of Corporate Social Responsibility Disclosure of Health Sector Companies in Indonesia) - Setiawan, Aris; Febriati, Febriati; Yahya, Rizky Fakhrul; Sari, Wilda (Akutansi Bisnis & Manajemen ( ABM ), 2025)
This research was conducted with the aim of looking at how the disclosure of health sector CSR is influenced by factors of company size, profitability, and debt. The research was conducted with a quantitative approach and assisted by EViews software. Multiple regression analysis was carried out on 32 companies listed on the IDX for five years, from 2019 to 2023. The results showed that CSR disclosure was positively influenced by company size, but not by profitability and leverage. This shows that large-scale companies will tend to have a higher ability to disclose their social activities compared to small companies. On the other hand financial indicators such as profitability and leverage do not directly affect CSR disclosures, these findings imply that financial performance factors are not the main drivers in CSR disclosure.